MARINE DIESEL ACS WITH EXTERNAL FEEDBACK OF THE SPEED SENSOR - Лещев, Владимир (Modern engineering and innovative technologies, 2017)
The article deals with the ASU model of a marine diesel engine with negative feedback, encompassing a speed sensor. Transient regimes in the scheme with additional feedback were investigated. A method for selecting the gain factors and the circuit for inc